A case study of the opportunities and trade-offs associated with deproclamation of a protected area following a land claim in South Africa. Issue 9 (1st September 2016) - Krüger, Ruth; Cundill, Georgina; Thondhlana, Gladman
Abstract : Reconciling conservation and social justice imperatives is a major challenge facing many postcolonial states worldwide. Where historically disenfranchised communities have laid legal claim to protected areas, the typical resolution has been collaborative management agreements between the state and claimant communities. The real outcomes of such strategies for people and ecosystems have been seriously questioned, although alternative approaches are seldom explored. Here, we reflect on one such alternative that was pursued in a case in South Africa, where the land was handed back to the community and a replacement protected area created. Our objective was to explore the opportunities and trade-offs associated with this approach for communities and conservation agencies alike, and to compare these to typical collaborative management outcomes. Methods included key informant interviews, focus group discussions and household surveys. We find that, surprisingly, this approach created more benefits for the conservation agency than for claimant communities. Indeed, the community experiences bore a striking resemblance to those experienced in collaborative management settings: intra-community conflict, confusion over leadership and serious questions about the boundaries of the "community". Processes aimed at redressing past injustice in disputes over conservation land, regardless of the approach adopted, must bring with them a strong commitment to building institutional and leadership capacities within communities, and pay serious attention to the ways in which equity and social justice can be fostered after the settlement of a land claim. Settlement agreements are frequently treated as the final step towards social justice, but are in fact just the beginning.